GovTech Procurement Practice Note - World Bank (World Bank, Washington, DC, 2021)
The objective of this practice note is to explore how to better procure GovTech solutions. The note provides recommendations to World Bank teams and client countries on how to assess and prepare for the application of GovTech systems. GovTech is defined as the use of technology to support government operations, service delivery, and transparency. It is a mechanism for whole of government public sector modernization that places the citizen at the center of the reform. This note enables countries to confront these challenges and to assess and implement potential GovTech solutions and to fill the knowledge gap regarding a usable and replicable approach to exploring and procuring GovTech to improve government services and core information systems. A five-step GovTech procurement framework is presented that guides readers through a strategic and holistic plan for the design, procurement, and implementation of GovTech solutions.